PENGARUH HARGA JUAL TERHADAP VOLUME PENJUALAN MOTOR HONDA BEAT PADA DEALER ANUGERAH KENCANA MOTOR LAHAT - Tri Rusilawati K (Riset Manajemen dan Akuntansi, 2015)
This study aims to analyze the effect of the sale price to sales volume of motor honda beat the dealer Anugerah Kencana Motor Lahat, the objectives of this research is to see and know the effect of the sale price to increase sales volume of motor honda beat the Dealer Award Motor Kencana (AKM) Lahat. As well as to see and know the relationship between the selling price and sales volume of motor honda beat the Dealer Award Kencana Motor (AKM) Lahat. In explaining and objectively portray the formulation of the problem, the writer uses the method of data collection in the form of Library Studies, Field Study consisting of: Interviews, observations and questionnaires. Data analysis technique used is the qualitative and quantitative analysis techniques . Based on analysis of the correlation coefficient (r) value of 0.39 means indicates that there is a weak correlation between the variable sales price to sales volume variables. To test the hypothesis that has been formulated rejected or accepted use tool t-test analysis and the obtained results are: the value of the t-table (0.05: 5), namely 3.182 and 0.79 t-test thus t-value